2003
DOI: 10.1002/chin.200332255
|View full text |Cite
|
Sign up to set email alerts
|

Indole and Isatin Oximes: Synthesis, Reactions, and Biological Activity.

Abstract: Organic chemistryOrganic chemistry Z 0200 Indole and Isatin Oximes: Synthesis, Reactions, and Biological Activity. -[218 refs.]. -(ABELE, E.; ABELE, R.; DZENITIS, O.; LUKEVICS, E.; Chem. Heterocycl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…Researchers investigated the biological activities of derivatives of indole and isatin oximes and observed that compounds that possess a chlorine in the C5 position exhibited high analgesic and anti-inflammatory activities ( 33 ). Furthermore, other studies reported that unsubstituted isatins are 5-10 times less active than halogenated ones at C5 position ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers investigated the biological activities of derivatives of indole and isatin oximes and observed that compounds that possess a chlorine in the C5 position exhibited high analgesic and anti-inflammatory activities ( 33 ). Furthermore, other studies reported that unsubstituted isatins are 5-10 times less active than halogenated ones at C5 position ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The indole nucleus possesses a wide range of biological activities being a biologically accepted pharmacophore in medicinal compounds. Antiinflammatory [70], antifungal [71], antimicrobial [72], anticancer [73,74], anti-HIV [75], antioxidant [76], and antiviral [77] activities, among many others, are some examples of the biological potential of indole derivatives. There was only one report concerning the synthesis of indoletype compounds using chalcones as starting materials.…”
Section: Transformation Of Chalcones To Indolesmentioning
confidence: 99%
“…O-ethers of furan amidoximes 303 [284] (Scheme 49), were obtained by the reaction of the corresponding nitriles 302 with Oalkylhydroxylamines in the presence of KOH/EtOH or NaOMe/ MeOH. The products 303 5-phenyl-2-furamidoximes exhibited strong antidepressant activity in mice [285].…”
Section: Iv11 Anxiolytics-antidepressantsmentioning
confidence: 99%